Learning Styles and English Proficiency of Undergraduate EFL Students at One State Islamic University in Sumatera, Indonesia - Lenny Marzulina; Nova Lingga Pitaloka; Aren Dwi Yolanda (State Islamic University of Raden Fatah Palembang, South Sumatra, Indonesia, 2019)
This study investigated (1) the correlation between each learning style and English proficiency, and investigated (2) the influence of each learning style to English proficiency of undergraduate EFL students of one state Islamic University in Sumatera, Indonesia. The study was in the form of correlational research method. The population of the study was 537 active EFL students. By using purposive sampling technique, there were 82 students involved as participants. The data were gained by using two instruments: Barsch Learning Styles Questionnaire and TOEFL prediction test. The result showed that 1) 34.0% of students preferred in visual learning style, 43% of students preferred in Auditory learning style, and 23% of students preferred in Kinesthetic learning style. 2) the coefficient correlation between visual learning style preference and English proficiency with r-obtained was (0.430). It was higher than r-table (.2565), then Ha1 was accepted and Ho1 was rejected. It indicated that there was a significant correlation between visual learning styles and their English proficiency. 3) The coefficient correlation between Auditory learning style and English proficiency was (0.2565). It was lower than r-table (.2565), then Ho2 was accepted and Ha2 was rejected. 4) The coefficient correlation between Kinesthetic learning styles and English Proficiency was (-0.166). It was lower than r-table (.2565), then Ho3 was accepted, and Ha3 was rejected. It showed that there was no significant correlation between kinesthetic learning style and English proficiency of EFL students. Besides, there was also a significant influence of visual learning style on English proficiency with 18.5% contributions.